How to diagnose difficult white matter disorders. Issue 4 (20th May 2020) - Williams, Thomas; Houlden, Henry; Murphy, Elaine; John, Nevin; Fox, Nick C; Schott, Jonathan M; Adams, Matthew; Davagananam, Indran; Chataway, Jeremy; Lynch, David S
Abstract : Genetic and acquired disorders of white matter comprise a diverse group of conditions, with often overlapping clinical and radiological findings. Patients present with a variable combination of cognitive impairment, ataxia, spasticity or movement disorders, among others. There are many genetic causes, and the route to diagnosis involves comprehensive clinical assessment, radiological expertise, metabolic investigations and finally genetic studies. It is essential not to miss the treatable acquired causes. In this review, we present a practical approach to investigating patients with acquired and genetic disorders of white matter, based on the experience of a large international referral centre. We present a guide for clinicians, including pitfalls of testing, clinical pearls and where to seek advice.